A Makey-Makey based STEM activity for children. (26th January 2022) - Tanik Onal, Nagihan; Saylan Kirmizigul, Aslı
Abstract: Learning STEM applications in the first years of education reinforce children's curiosity toward exploring the world around them, and form the basis for all scientific studies they will receive throughout their lives. The aim of this study is to implement the STEM activity on the subject of seasons to preschool students. In the spring semester of the 2019–2020 academic year, the activity titled "Learning with Seasons" was carried out with the participation of 24 children aged 48–60 months. The activity was carried out using the Makey-Makey kit and the coding program Scratch by a preschool teacher within four course hours. The activity plan was prepared based on the learning objectives and indicators included in the preschool curriculum and the Next Generation Science Standards. During the activity, 7E learning model stages were followed. It can be stated that the activities carried out using the Makey-Makey kit will facilitate access to learning objectives related to science education in the preschool period and establish an environment in which students can have fun while learning. In this context, the present activity is a very effective in terms of the science education of preschool children and reaching the specified international standards.